Child temperament, parenting style and emotional and behavioural problems in early childhood - findings from the Longitudinal Study of Australian Children - Sanson, A; Mitrou, F; Christensen, D; Lawrence, D; Zubrick, S (My University, 2011)
Identifying and describing the antecedents of emotional and behavioural problems in early childhood has been of much interest to researchers in the field of child behaviour with recent studies highlighting the diagnostic validity, persistence and sequelae of these problems. Within this broad research area there is particular interest in possible interactions between parenting styles and child temperament, such that children with particular temperament characteristics exposed to less favourable parenting practices are disproportionately at risk of emotional and behavioural problems. This has been described as the ‘goodness of fit’ model. Research with children and adolescents provides support for the impact of parenting and temperament on emotional and behavioural problems, as well as inconsistent support for the interactions predicted by the goodness of fit model. This study sought to add to the current knowledge in the field of early childhood behaviour by examining the goodness of fit model in a group of 2,644–3,214 children from the B cohort of the Longitudinal Study of Australian Children. The temperamental characteristics of approach and irritability were measured at 3–19 months, parental warmth and hostility were measured at 2–3 years, and emotional problems, peer problems, conduct problems and hyperactivity were measured at 4–5 years via parent-report. Using logistic regression models, we found that child temperament and parenting style predicted the subsequent development of emotional and behavioural problems, independent of a range of other biopsychosocial ecological factors. However, we did not find the hypothesized interactions between parenting and temperament. On the basis of the particular temperament and parenting characteristics examined here, our results suggest that goodness of fit models may not accurately describe the contribution of parenting and temperament to the development of emotional and behavioural problems in early childhood. Our results also suggest that all children benefit from parenting high in warmth and low in hostility regardless of temperament, consistent with ‘universal’ parenting programs.
Keywords: Child Development; Childhood and child development; Child Development; Childhood and child development